Ocena możliwości zagospodarowania wyrobisk po eksploatacji iłów serii poznańskiej na przykładzie złoża "Tadeuszów Rudzianko" k. Mińska Mazowieckiego - Łuczak-Wilamowska, Beata; Gąska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Legal conditionings and theoretical assumptions of reclamation and management of post-mining open-cast workings were analysed in the present paper. Furthermore, possibilities and needs of management of the open-cast complex of workings after extraction of the Poznań Series clays in the Tadeuszów-Rudzianko deposit were discussed. Three concepts of management of workings were analyzed ? forestation, waste deposition and building of a pond. In the paper, not only technical possibilities were taken into consideration, but also social and economic demands of the region, in which there occur areas that are degraded due to extraction of mineral raw materials.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zwałowiska pokopalniane; erozja wodna